Model refinements and experimental testing of highly flexible piezoelectric energy harvesters - Patel, R.; Tanaka, Y.; McWilliam, Stewart; Mutsuda, H.; Popov, Atanas A. (Elsevier, 2016)
This paper addresses limitations to existing analytical models for piezoelectric energy harvesters. The presented model is targeted at predicting behaviours of highly flexible piezoelectric devices (FPEDs) and includes high orders of substrate and piezoelectric material nonlinearity, geometric nonlinearity, and additionally the effects of both self-weight and pre-stress. Validation through experimental testing is provided.